Seasonal Trophic Shift of Littoral Consumers in Eutrophic Lake Taihu (China) Revealed by a Two-Source Mixing Model - Qiong Zhou; Ping Xie; Jun Xu; Xufang Liang; Jianhui Qin; Te Cao; Feizhou Chen (The Scientific World Journal)
We evaluated the seasonal variation in the contributions of planktonic and benthic resources to 11 littoral predators in eutrophic Lake Taihu (China) from 2004 to 2005. Seasonal fluctuations in consumer σ13C and σ15N were attributed to the combined impacts of temporal variation in isotopic signatures of basal resources and the diet shift of fishes. Based on a two-end-member mixing model, all target consumers relied on energy sources from coupled benthic and planktonic pathways, but the predominant energy source for most species was highly variable across seasons, showing seasonal trophic shift of littoral consumers. Seasonality in energy mobilization of consumers focused on two aspects: (1) the species number of consumers that relied mainly on planktonic carbon showed the lowest values in the fall and the highest during spring/summer, and (2) most consumer species showed seasonal variation in the percentages of planktonic reliance. We concluded that seasonal trophic shifts of fishes and invertebrates were driven by phytoplankton production, but benthic resources were also important seasonally in supporting littoral consumers in Meiliang Bay. Energy mobilization of carnivorous fishes was more subject to the impact of resource availability than omnivorous species.